2012
DOI: 10.1111/j.1755-0998.2012.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive sampling of insect DNA from defensive secretion

Abstract: Nondestructive techniques to obtain DNA from organisms can further genetic analyses such as estimating genetic diversity, dispersal and lifetime fitness, without permanently removing individuals from the population or removing body parts. Possible DNA sources for insects include frass, exuviae, and wing and leg clippings. However, these are not feasible approaches for organisms that cannot be removed from their natural environment for long periods or when adverse effects of tissue removal must be avoided. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Similarly, the use of residual egg debris has advantages over other documented noninvasive genetic sampling methods involving larval exuviae, frass, or the more traditional removal of tissue samples (e.g., palps, wing clippings, legs) from adult organisms. These can be problematic logistically as they often require longer organism holding times, necessitate organism removal from the environment, or may result in a limited number of viable available samples [18,19,20,21,22]. For example, Saarinen et al [13] demonstrated that wing clips represent a viable, non-lethal method of obtaining DNA from a federally endangered butterfly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the use of residual egg debris has advantages over other documented noninvasive genetic sampling methods involving larval exuviae, frass, or the more traditional removal of tissue samples (e.g., palps, wing clippings, legs) from adult organisms. These can be problematic logistically as they often require longer organism holding times, necessitate organism removal from the environment, or may result in a limited number of viable available samples [18,19,20,21,22]. For example, Saarinen et al [13] demonstrated that wing clips represent a viable, non-lethal method of obtaining DNA from a federally endangered butterfly.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being nonlethal, such methods still require capture and handling of the target organism which can inflict significant stress, inadvertent damage, or death, and may not be feasible for low density or at-risk populations. Alternatively, researchers have also successfully secured DNA from frass, exuviae, and hemolymph in defensive secretions [18,19,20,21,22]. However, these sources may not be broadly available for many taxa and certainly offer significant challenges for reliable collection in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Animals were not fed during capture to avoid altering their diet. Samples of hemolymph were collected within 24 hours of capture following the procedure described in [ 32 ]. Briefly, individuals present a tenebrio-type defensive gland from their anal sternite when exposed to human breath [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each individual received a unique ID, which was painted on its elytra using Testors Gloss Enamel in earth tone colors. We collected 0.2–5 μL of hemolymph from the defensive glands of all beetles using the method described in Donald et al (2012), which did not affect either survival or reproduction in laboratory trials. Hemolymph was stored in prepared lysis buffer (Promega DNA IQ system).…”
Section: Methodsmentioning
confidence: 99%
“…Fragment analysis was completed by GeneWiz Inc. (South Plainfield, NJ) using Applied Biosystems 3730xl DNA Analyzers. All individuals' genotypes at nine microsatellite loci (Donald et al 2012) were scored using GeneMarker (SoftGenetics, State College, PA).…”
Section: Methodsmentioning
confidence: 99%